2005
DOI: 10.1111/j.1365-2265.2005.02423.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the prevalence of gsp mutations in GH‐secreting pituitary adenomas differ geographically or racially? Prevalence of gsp mutations in Japanese patients revisited

Abstract: We conclude that the prevalence of gsp mutations in Japanese acromegaly patients is comparable to those of other reports from various regions. Therefore, Japanese patients do not stand as an example for geographical or racial difference in the prevalence of gsp mutations in GH-secreting pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 27 publications
11
41
1
Order By: Relevance
“…The rate of the gsp mutation in our series (58.1%) is comparable to the rate reported in Caucasian patients (19)(20)(21) and in a recent series of 100 Japanese patients (53.0%) (18). In studies reported in 1993, the incidence of gsp mutations in Japanese acromegalics was low as 9.3 and 4.4% (43,44); however, re-evaluation performed 10 years later by the same authors indicated that the corrected incidence was 53.1% (45).…”
Section: Gsp Mutations and Ck Staining Patternsupporting
confidence: 72%
See 2 more Smart Citations
“…The rate of the gsp mutation in our series (58.1%) is comparable to the rate reported in Caucasian patients (19)(20)(21) and in a recent series of 100 Japanese patients (53.0%) (18). In studies reported in 1993, the incidence of gsp mutations in Japanese acromegalics was low as 9.3 and 4.4% (43,44); however, re-evaluation performed 10 years later by the same authors indicated that the corrected incidence was 53.1% (45).…”
Section: Gsp Mutations and Ck Staining Patternsupporting
confidence: 72%
“…The specimens were preserved under K80 8C until RNA extraction. Total RNA contents were extracted from the adenomae tissues, and the first-strand cDNA was synthesised from 5 mg total RNA by RT-PCR after removing contaminating genomic DNA as reported previously (18). To amplify the specific G s a-subunit cDNA fragment (249 bp), including codons 201 and 227 of the Gsa gene, we designed a sense primer and an antisense primer corresponding to nucleotide sequences 562-585 (5 0 -GTGTATCAAGCAGGCTGACTATGTG-3 0 ) and 793-819 (5 0 -CAGGCGGTTGTTCTGGTT-3 0 ) respectively.…”
Section: Histological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…12,22) As a member of the G-protein coupled receptor family, GHRHR consists of seven transmembrane domains. 10) The binding of GHRH to this receptor activates adenylyl cyclase, which causes an increase in intracellular cyclic adenosine monophosphate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…9,18) Since the change mimics the condition of continuous GHRH stimulation, these mutations could cause GH secretion and somatotroph proliferation. Patients bearing GH-secreting adenoma with gsp mutations show higher, 16) lower, 8) or similar basal levels of plasma GH 5,21,22) compared with those of acromegalic patients without gsp mutations, and the responses of GH secretion to GHRH are lower than those in patients with gsp mutation-negative GH-secreting adenomas. 4,16,22) The expression levels of GHRHR in GH-secreting pituitary adenomas may also be one of the important factors for proliferation of GH-secreting pituitary adenomas.…”
Section: Introductionmentioning
confidence: 98%